Attitudes of Urban American Indians and Alaska Natives Regarding Participation in Research - Buchwald, Dedra (Blackwell science Inc, 2006)
OBJECTIVE: To determine what factors influence participation in health research among American Indians and Alaska Natives. METHODS: Using vignettes that described 3 types of research studies (a behavioral intervention trial, a genetic association study, and a pharmacotherapy trial), we surveyed 319 patients and 101 staff from an urban Indian health care facility to ascertain how study design, institutional sponsorship, community involvement, human subjects' issues, and subject matter influence participation. RESULTS: Overall response rates were 93% for patients and 75% for staff. Hypothetical participation was highest for the genetic study (patients = 64%; staff = 48 %), followed by the behavioral intervention (patients = 46%; staff = 42%), and the pharmacotherapy trial (patients = 32%; staff = 23%). The odds of participation (odds ratio [OR]) were generally increased among patients and staff when the study was conducted by health care providers (OR = 1.3 to 2.9) and addressed serious health problems (OR = 1.2 to 7.2), but were decreased if the federal government led the study (OR = 0.3 to 0.5), confidentiality might be broken (OR = 0.1 to 0.3), and compensation was not provided (OR = 0.5 to 0.7). CONCLUSION: Close attention to study type, institutional sponsorship, community involvement, potential risks and benefits, and topic are essential to conceptualizing, designing, and implementing successful health research with American Indian and Alaska Native populations.